224k views
3 votes
3(x + 2) = 4(x + 1)
HELP

User Chao Zhang
by
6.3k points

1 Answer

1 vote

Answer: x=2

Explanation:

Let's solve your equation step-by-step.

3(x+2)=4(x+1)

Step 1: Simplify both sides of the equation.

3(x+2)=4(x+1)

(3)(x)+(3)(2)=(4)(x)+(4)(1)(Distribute)

3x+6=4x+4

Step 2: Subtract 4x from both sides.

3x+6−4x=4x+4−4x

−x+6=4

Step 3: Subtract 6 from both sides.

−x+6−6=4−6

−x=−2

Step 4: Divide both sides by -1.

−x −1 = −2 −1

Answer

x=2

User Happyhuman
by
5.8k points